Altered cortical activation from the hand after facial botulinum toxin treatment. (25th November 2013) - Haenzi, Sara; Stefanics, Gabor; Lanaras, Tatjana; Calcagni, Maurizio; Ghosh, Arko
Abstract Plastic interactions between face and hand cortical tactile circuits occur after severe injuries that affect the hand such as in amputation or spinal cord injury. However, whether loss of facial movements alters the cortical circuits involved in processing tactile inputs from the hand remains unknown. In this prospective observational study we used electroencephalography (EEG) to measure cortical activity evoked by tactile stimulation of the hands before and after botulinum toxin‐A‐induced facial paralysis. We found a reduction in the tactile event‐related potentials (ERPs) 6 weeks after the treatment. This suggests that the limited paralysis of facial muscles induced during cosmetic interventions designed to smooth lines and wrinkles on the face is sufficient to alter the cortical processing of tactile inputs from the hand.